2015
DOI: 10.6000/1927-5129.2015.11.61
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenated Secondary Metabolites from Endophytic Fungi Isolated From Ocimum sanctum

Abstract: Ocimum sanctum Linn (Tulsi), an important medicinal plant of Bangladesh is used for antimicrobial, antiinflammatory and antiulcer activities. Eleven endophytic fungi were isolated from O. sanctum. The fungal strain, labeled as OS-005, was cultivated at large scale on the potato dextrose agar semi solid medium and was extracted with ethyl acetate. Repeated column chromatography of the parent extract by normal phase silica gel and one of its fraction by Sephadex LH-20 afforded linoleic acid, R (-)-glycerol monol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Studies by Mohammad et al, (2015) on the crude extract of endophytes isolated from O.tenuiflorum, elucidated the structure of linoleic acid, R (-)-glycerol monolinoleate, 9, 10, 11,trihydroxy-(12Z)-12-octadecenoic acid, ergosterol, ergosterol peroxide, 1,8-Odimethylaverantin, coriloxin, and a new natural product named as sactumol. Studies of Gangadevi & Muthumary, (2007) showed that leaf endophyte Phyllosticta (sp.6) is a potential producer of taxol in artificial culture media.…”
Section: Bioactive Compoundsmentioning
confidence: 99%
“…Studies by Mohammad et al, (2015) on the crude extract of endophytes isolated from O.tenuiflorum, elucidated the structure of linoleic acid, R (-)-glycerol monolinoleate, 9, 10, 11,trihydroxy-(12Z)-12-octadecenoic acid, ergosterol, ergosterol peroxide, 1,8-Odimethylaverantin, coriloxin, and a new natural product named as sactumol. Studies of Gangadevi & Muthumary, (2007) showed that leaf endophyte Phyllosticta (sp.6) is a potential producer of taxol in artificial culture media.…”
Section: Bioactive Compoundsmentioning
confidence: 99%